Application of Arbuscular Mycorrhizal Fungi in Vineyards: Water and Biotic Stress Under a Climate Change Scenario: New Challenge for Chilean Grapevine Crop - Aguilera, Paula; Ortiz, Nancy; Becerra, Ninozhka; Turrini, Alessandra; Gaínza-Cortés, Felipe; Silva-Flores, Patricia; Aguilar-Paredes, Ana; Romero, Juan Karlo; Jorquera-Fontena, Emilio; Mora, María de La Luz; Borie, Fernando (Frontiers in Microbiology, 2022)
The crop Vitis vinifera (L.) is of great economic importance as Chile is one of the main wine-producing countries, reaching a vineyard area of 145,000 ha. This vine crop is usually very sensitive to local condition changes and agronomic practices; therefore, strategies to counteract the expected future decrease in water level for agricultural irrigation, temperature increase, extreme water stress (abiotic stress), as well as increase in pathogenic diseases (biotic stress) related to climate change will be of vital importance for this crop. Studies carried out in recent years have suggested that arbuscular mycorrhizal fungi (AMF) can provide key ecosystem services to host plants, such as water uptake implementation and enhanced absorption of nutrients such as P and N, which are key factors for improving the nutritional status of the vine. AMF use in viticulture will contribute also to sustainable agronomic management and bioprotection against pathogens. Here we will present (1) the current status of grapevines in Chile, (2) the main problems in grapevines related to water stress and associated with climate change, (3) the importance of AMF to face water stress and pathogens, and (4) the application of AMF as a biotechnological and sustainable tool in vineyards.